Potential impact on prevalence of obesity in the UK of a 20% price increase in high sugar snacks: modelling study - Scheelbeek, Pauline F D (BMJ, 2019)
OBJECTIVE: To estimate the potential impact on body mass index (BMI) and prevalence of obesity of a 20% price increase in high sugar snacks. DESIGN: Modelling study. SETTING: General adult population of the United Kingdom. PARTICIPANTS: 36 324 households with data on product level household expenditure from UK Kantar FMCG (fast moving consumer goods) panel for January 2012 to December 2013. Data were used to estimate changes in energy (kcal, 1 kcal=4.18 kJ=0.00418 MJ) purchase associated with a 20% price increase in high sugar snacks. Data for 2544 adults from waves 5 to 8 of the National Diet and Nutrition Survey (2012-16) were used to estimate resulting changes in BMI and prevalence of obesity. MAIN OUTCOME MEASURES: The effect on per person take home energy purchases of a 20% price increase for three categories of high sugar snacks: confectionery (including chocolate), biscuits, and cakes. Health outcomes resulting from the price increase were measured as changes in weight, BMI (not overweight (BMI <25), overweight (BMI ≥25 and <30), and obese (BMI ≥30)), and prevalence of obesity. Results were stratified by household income and BMI. RESULTS: For income groups combined, the average reduction in energy consumption for a 20% price increase in high sugar snacks was estimated to be 8.9×10(3) kcal (95% confidence interval −13.1×10(3) to −4.2×10(3) kcal). Using a static weight loss model, BMI was estimated to decrease by 0.53 (95% confidence interval −1.01 to −0.06) on average across all categories and income groups. This change could reduce the UK prevalence of obesity by 2.7 percentage points (95% confidence interval −3.7 to −1.7 percentage points) after one year. The impact of a 20% price increase in high sugar snacks on energy purchase was largest in low income households classified as obese and smallest in high income households classified as not overweight. CONCLUSIONS: Increasing the price of high sugar snacks by 20% could reduce energy intake, BMI, and prevalence of obesity. This finding was in a UK context and was double that modelled for a similar price increase in sugar sweetened beverages.